A successful guide in understanding latino immigrant patients: an aid for health care professionals (2012)
ABSTRACT: Objective It has been shown that cultural and linguistic barriers may have a great impact on the quality of health care received by immigrants. The recent growth of Latino immigrants in new areas of the country (particularly in the South) has presented great challenges to the health care system and health care professionals in these states. Through a NCI funded community-based educational program (Sowing the Seeds of Health), we created an informative DVD to aid health care providers in better understanding Latino immigrant health beliefs and health care seeking behaviors. The educational DVD presented information on how to provide culturally competent care as it relates to Latino immigrants, their expectations when seeking care, and common cultural beliefs and practices. Health care professionals and Latino immigrants participated in the development and content of the DVD. Methods The intervention was delivered though various mediums; on-site, on-line, two national webcasts and mailed copies of the DVD. Pre- post self-administered questionnaires assessing knowledge and attitudes regarding culture competency and relevant topics addressed in the DVD. Results—Four-hundred and sixty-three (N=463) health care professionals participated from across the United States. Intervention produced significant overall knowledge increase (p-value <0.001) in cultural competency, Latino cultural beliefs and barriers to healthcare access for Latino immigrants. Conclusion The findings indicate that a short DVD offered via multiple mediums may be a promising avenue for educating health care professionals about the needs and expectations of Latino immigrants in the U.S.